The way to regulate exercise on the results of two-stage bicycle stress test in patients with different character and severity of risk factors for cardiovascular disease. - Bochkova N.L (Kharkov National Pedagogical University, 2011)
Method of regulation of physical loads on results a two-stage veloergometric test at persons with different character and degree of expressed of cardiovascular diseases risk's factors. The method of dosage of physical loads is described in employments of health orientation. A method is worked out on results previous researches of the morfofunсtional state, physical capacity and features of adaptation to physical loads of persons with cardiovascular diseases risk's factors. A method is based on the results of the veloergometric testing without the use of the maximal loading. It is shown that the presented method allows to individualize the level of maximum-possible physical loads and determine the orientation of athletic-health employments depending on a prevailing of cardiovascular risk's factor.